Analysis of coupling coordination development and obstacle factors in the water-energy-carbon-ecological environment nexus across China’s Yellow River basin - Yuping Han; Zhuo Jiang; Mengdie Zhao; Jinhang Li (Scientific Reports)
Abstract Under the influence of human activities and climate change, the development of the Yellow River basin (YRB) is constrained by the utilization of hydropower resources, carbon emission and ecological deterioration. In this paper, combined weighting method, comprehensive assessment index, coupled coordination degree and obstacle degree model were used to construct a theoretical framework of the water-energy-carbon-ecological environment (WECEc) system in the nine provinces of the YRB from 2013 to 2022, analyze the comprehensive development level of the system and the spatio-temporal evolution characteristics of the coupled coordination level of the system, and analyze obstacle factors. The results show that (1) During the study period, the comprehensive development level of WECEc system in the YRB generally increased in a fluctuation pattern. Among them, the water resources subsystem showed a fluctuating upward trend, the energy subsystem showed a slow and steady upward trend, the carbon subsystem showed a steady upward trend, and the ecological environment subsystem showed a significant upward trend. (2) The coupling coordination degree of WECEc system in nine provinces and regions of the YRB is concentrated as “IV” level “Primary Coordination” type. The overall coupling coordination degree of WECEc system in the YRB showed a steady increase in time, but in space, it showed a stepped distribution with higher coordination degree in the middle and upper reaches and lower coordination degree in the lower reaches, with significant regional differences. (3) Total water resources (WS1), Per capita carbon storage (CS4), coal production (ER2), water production modulus (WS2), carbon storage of forest and grass vegetation (CS1), total energy production (ER1), carbon sink of forest and grass vegetation (CS2) and domestic water consumption (WD3) play an important role in the coordinated development of WECEc system in the YRB. They are also the main obstacle factors that affects the coupling coordination degree of the system. This paper provides research basis and policy suggestions for promoting the sustainable development of the coupling system of WECEc in the nine provinces of the YRB, and promoting the high-quality development of Economy-Society-Ecology (ESE) in the YRB.